Possibility of a Standardized System for Task-Related Hierarchal Positions of Dental Hygienists - Eun-Ha Jung; Sun-Young Han; Eun-Bi Sim; Sung-Suk Bae (The Korean Society of Dental Hygiene Science, 2020)
Background: Despite the demand for greater competence of dental hygienists in recent times, and the consequent standardization of systems in the organizations, there is a lack of a proper system for hierarchal positions of dental hygienists. The aim of this study was to identify the tasks performed by Korean dental hygienists in various work settings and hierarchal positions to suggest a standardized system for task-related hierarchal positions.Methods: A survey was conducted by sending questionnaires to 966 dental hygienists, and responses from 757 participants were included in the final analysis. The survey comprised questions regarding participants' general characteristics, tasks, current positions, and the internal policies or standards of the respective organizations to define these positions. The participants' positions were analyzed as frequency and cross-sectional analysis with respect to their general characteristics, their place in the organizational charts, the size of their workplaces, and differences in the tasks performed.Results: Data showed that 82.6% of the hospitals and clinics in Korea have organizational systems to determine the positions, and there was a significant difference in the systems according to the size of the health facility (p＜0.05). The standards or policies used to define positions within general or university hospitals were determined by internal regulations or bylaws, whereas work experience was the major determinant of positions in smaller dental hospitals or clinics. The main tasks performed by dental hygienists in Korea were dental assistance (81.2%), routine dental hygiene tasks (53.4%), and administrative tasks, such as reception and billing (46.1%).Conclusion: Most dental hygienists in Korea are actively involved in dental assistance. Therefore, their specific tasks and responsibilities should be standardized more effectively. The data obtained from this study can be used to establish a standardized position system.